Computational and Pharmacological Evaluation of Carveol for Antidiabetic Potential - Ahmed, Muhammad Shabir; Khan, Arif-ullah; Kury, Lina Tariq Al; Shah, Fawad Ali (Frontiers in Pharmacology, 2020)
Background: Carveol is a natural drug product present in the essential oils of orange peel, dill, and caraway seeds. The seeds oil of Carum Carvi has been reported as antioxidant, anti-inflammatory, anti-hyperlipidemic, anti-diabetic, and hepatoprotective. Methods: The antidiabetic potential of carveol was investigated by employing in-vitro, in-vivo, and in-silico approaches. Moreover, alpha-amylase inhibitory assay or alloxan-induced diabetes model was used for in-vitro and in-vivo analysis respectively. Results: Carveol showed maximum energy value (≥ -7 Kcal/mol) against sodium-glucose co-transporter, aldose reductase, and sucrose isomaltase intestinal, whereas exhibited intermediate energy value (≥ -6 Kcal/mol) against C-alpha glucosidase, glycogen synthase kinases-3β, fructose-1,6-bisphosphatase, phosphoenolpyruvate carboxykinase and other targets by in-silico approach. Similarly, carveol showed lower energy value (≥ 6.4 Kcal/mol) against phosphoenolpyruvate carboxykinase and glycogen synthase kinase-3β. The in-vitro assay demonstrated that carveol inhibits alpha-amylase activity concentration-dependently. Carveol attenuated the in-vivo alloxan-induced (1055.8 µMol /Kg) blood glucose level by a dose and time-dependent manner (days 1, 3, 6, 9, and 12), compared to the diabetic control group, and further, these results are comparable to the metformin positive control group. Carveol at 394.1 µMol/Kg improved oral glucose tolerance overload in rats compared to the hyperglycemic diabetic control group. Moreover, carveol also attenuated the glycosylated hemoglobin level along with mediating antihyperlipidemic and hepatoprotective effects in alloxan-induced diabetic animals. Conclusions: This study reveals that carveol exhibited binding affinity against different targets involved in diabetes, possess anti-diabetic, antihyperlipidemic, and hepatoprotective actions.